Importance of extracardiac FDG uptake to diagnose cardiac sarcoidosis. - Tahara, Nobuhiro; Bekki, Munehisa; Sugiyama, Yoichi; Tahara, Atsuko; Fukumoto, Yoshihiro (Journal of Nuclear Cardiology, 2020)
However, endomyocardial biopsy shows the limited sensitivity no better than 30% by sampling errors due to patchy distribution of cardiac granulomas.[2],[4],[5] Sarcoidosis often has been determined by extracardiac biopsy specimens from skin, muscle, and lymph node. While cardiac involvement is clinically apparent in < 5% of all patients with sarcoidosis, over 20% of the patients have been found cardiac granulomas at autopsy.[6],[7] Therefore, the diagnosis of CS was often a challenging issue for physicians. Of the 12 patients, 7 (58.3%) indicated biopsy positive for sarcoidosis such as endomyocardial biopsy or extracardiac biopsy.